The Emergence of Genetic Counseling in Sweden: Examples from Eugenics and Medical Genetics. Issue 3 (10th August 2015) - Björkman, Maria
Argument This paper examines the intertwined relations between eugenics and medical genetics from a Swedish perspective in the 1940s and 1950s. The Swedish case shows that a rudimentary form of genetic counseling emerged within eugenic practices in the applications of the Swedish Sterilization Act of 1941, here analyzed from the phenomenon of "heredophobia" (ärftlighetsskräck). At the same time genetic counseling also existed outside eugenic practices, within the discipline of medical genetics. The paper argues that a demand for genetic counseling increased in the 1940s and 1950s in response to a sense of reproductive responsibility engendered by earlier eugenic discourse. The paper also questions the claim made by theoreticians of biopolitics that biological citizens have emerged only during the last decades, especially in neoliberal societies. From the Swedish case it is possible to argue that this had already happened earlier in relation to the proliferation of various aspects of eugenics to the public.